Videogames about Politics as States of Exception - Hao, Yu (Gamevironments, 2020)
This article looks at videogames about politics within the theoretical framework of Giorgio Agamben’s states of exception and argues that while videogames can reveal political issues by implementing rules into the gameplay, they simultaneously render the in-game rules and consequences inoperative in regard to real-world politics, which can be described as states of exception in Agamben’s sense. Agamben distinguishes between the fictitious and the real state of exception, and this distinction leads to his proposal of a politics of pure means in which he considers play as a means of profanation that renders what has been played with inoperative and free. Drawing on this discussion, the article looks at the parallel between the rules in videogames and the laws in states of exception and re-examines the concepts of game rules and play under the rubric of Agamben’s political philosophy. In so doing, it explores how playing with rules in videogames about politics can turn these games into states of exception to talk about and reflect on various political issues.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 5-Auteur.rice PANDC; _Nettoyé